(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
If all is well with women it will be well with the society and ultimately the nation.Swami Vivekananda valued the role of women, he said their role is complementary, neither male nor female is superior. Swami Vivekananda wrote “It is very difficult to understand why in this country so much difference is made between men and women, whereas the Vedanta declares that one and the same Conscious Self is present in all beings.”